Library Security and Sustainable Service Delivery in Donald Ekong Library, University of Port Harcourt, Rivers State, Nigeria - Echem, Mercy Ekenma; Okwu, Emmanuel (Communicate: Journal of Library and Information Science, 2023)
The study investigated library security and sustainable services in Donald Ekong library, University of Port Harcourt. The study adopted a descriptive research survey design. The population of the study was thirty-one (31) comprising professional and paraprofessional staff in Donald Ekong Library, University of Port Harcourt. Census sampling technique was adopted to select all the respondents. The data was analyzed using simple percentages presented in charts, mean scores and standard deviation. The study revealed that smart card access control, CCTV, fire extinguisher, installation of window burglary, door intrusion alarm, panic alarm, perimeter alarm system and RFID were the security systems adopted in Donald Ekong Library, University of Port Harcourt. Interestingly, smart card access control, door intrusion alarms, perimeter alarm system, installation of window burglary and panic alarm were implemented to a high extent. The study also discovered that reprographic services, current awareness services, OPAC, digital library services, orientation programmes, indexing services, referral services, abstracting services, selective dissemination of information, digital reference services were the services rendered at Donald Ekong Library, University of Port Harcourt. Regrettably, inadequate funding, inadequate staff to deliver effective library services, weak library security policy, non-challant attitude of staff, conspiracy between staff and patrons, inadequate staff training on security measures and poor lighting in important areas of the library were the challenges faced in the security and service delivery in Donald Ekong Library, University of Port Harcourt. The study recommended among other things maintenance culture to ensure the sustenance of security.